G-quadruplex oligonucleotide AS1411 as a cancer-targeting agent: Uses and mechanisms - Bates, Paula J.; Reyes-Reyes, Elsa M.; Malik, Mohammad T.; Murphy, Emily M.; O'Toole, Martin G.; Trent, John O. (Biochimica et biophysica acta. General subjects, 2017)
AS1411 is a 26-mer G-rich DNA oligonucleotide that forms a variety of G-quadruplex structures. It was identified based on its cancer-selective antiproliferative activity and subsequently determined to be an aptamer to nucleolin, a multifunctional protein that preferentially binds quadruplex nucleic acids and which is present at high levels on the surface of cancer cells. AS1411 has exceptionally efficient cellular internalization compared to non-quadruplex DNA sequences. Recent developments related to AS1411 will be examined, with a focus on its use for targeted delivery of therapeutic and imaging agents. Numerous research groups have used AS1411 as a targeting agent to deliver nanoparticles, oligonucleotides, and small molecules into cancer cells. Studies in animal models have demonstrated that AS1411-linked materials can accumulate selectively in tumors following systemic administration. The mechanism underlying the cancer-targeting ability of AS1411 is not completely understood, but recent studies suggest a model that involves: (1) initial uptake by macropinocytosis, a form of endocytosis prevalent in cancer cells; (2) stimulation of macropinocytosis by a nucleolin-dependent mechanism resulting in further uptake; and (3) disruption of nucleolin-mediated trafficking and efflux leading to cargoes becoming trapped inside cancer cells. Human trials have indicated that AS1411 is safe and can induce durable remissions in a few patients, but new strategies are needed to maximize its clinical impact. A better understanding of the mechanisms by which AS1411 targets and kills cancer cells may hasten the development of promising technologies using AS1411-linked nanoparticles or conjugates for cancer-targeted therapy and imaging. This article is part of a Special Issue entitled "G-quadruplex" Guest Editor: Dr. Concetta Giancola and Dr. Daniela Montesarchio. •AS1411 is a G-quadruplex DNA oligonucleotide that is also a nucleolin aptamer.•This review covers the structure, clinical status, uses, and mechanism of AS1411.•AS1411 is being widely used to deliver therapeutic and imaging agents to cancer cells.•Its cancer-targeting activity has been demonstrated in at least 30 animal studies.•Its targeting mechanism is not fully understood but may involve macropinocytosis.